2022
DOI: 10.1007/s00127-022-02277-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of adverse childhood experiences and their co-occurrence in a large population of adolescents: a Young HUNT 3 study

Abstract: Purpose Studies of adverse childhood experiences (ACEs) undertaken at the time of adolescence in the general population are not common. The aim of this study was to determine the prevalence and co-occurrence of the individual ACEs and sub-types of ACEs in a large population of adolescents. Methods Data were used from the Young Nord-Trøndelag Health (Young HUNT 3) study, a population-based study of young adolescents. ACEs were operational defined as sexual,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…In general, prevalence rates exhibit substantial variability across studies. However, compared to other non-clinical samples (Bomysoad & Francis, 2020 ; Broekhof et al, 2022 ), the observed prevalence of 69.1% in our study falls towards the higher end of the range of ACEs prevalence. This can be attributed to the study population in this cross-sectional study, namely youth registered for mental health care.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In general, prevalence rates exhibit substantial variability across studies. However, compared to other non-clinical samples (Bomysoad & Francis, 2020 ; Broekhof et al, 2022 ), the observed prevalence of 69.1% in our study falls towards the higher end of the range of ACEs prevalence. This can be attributed to the study population in this cross-sectional study, namely youth registered for mental health care.…”
Section: Discussioncontrasting
confidence: 83%
“…For instance, we found that youths who reported sexual abuse, physical abuse, or neglect frequently reported emotional abuse and bullying. These results suggest that youths reporting multiple ACEs not only report the same type of ACEs but also childhood adversity across various domains, indicating that ACEs should be assessed together as a whole rather than separately (Broekhof et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…This review indicates that the majority of studies have not routinely measured or recorded the presence of ACES in the histories and experiences of children and adolescents being referred to paediatric gender services so there is limited data despite the wider research indicating that gender-diverse youth and adults have experienced high rates of childhood adversity 121–125. It is not possible for this review to speculate as to the relationship between ACES and the experience of gender-related distress in children and adolescents, but the results indicate that this is another important area in which systematic collection of data, at referral and across pathways of care can support care.…”
Section: Discussionmentioning
confidence: 92%
“…This may reflect variations between the present study and others in ACE definitions or study sample characteristics. Recent research by Broekhof et al (2022) suggests that due to overlap between ACE sub-types and individual ACEs, perhaps ACEs should be assessed as a combined group rather than individually 18 .…”
Section: Discussionmentioning
confidence: 99%